MEDAN MAKNA PERALATAN DAPUR MASYARAKAT ROKAN HULU - Elvina Syahrir (Madah: Jurnal Bahasa dan Sastra, 2012)
This research discusses about semantic field of kitchen equipment used in Rokan Hulu region. The data observed consist of noun lexemes of kitchen equipment which is generally used by Rokan Hulu people.  The semantic theory is used to analysis the meaning components. Based on the result of the research, it is concluded that the lexemes of kitchen equipment grouped as (1) water stock and carriers, (2) cold steels, (3) stoves, (4) drinking sets,  (5) the dishes, and (6) the carriers.  Penelitian ini mengkaji tentang medan makna peralatan rumah tangga yang digunakan oleh di wilayah Rokan Hulu. Data yang diperoleh terdiri dari leksem kata benda peralatan dapur yang digunakan oleh masyarakat Rokan Hulu. Teori semantik digunakan untuk menganalisis komponen makna. Berdasarkan hasil penelitian bahwa leksem peralatan dapur dikelompokkan sebagai (1) tempat air; wadah; bak; tabung, (2) senjata tajam, (3) alat untuk memasak, (4) alat minum, (5) wadah makanan,  dan  (6)   wadah pembawa sesuatu/barang.